Níveis de TNF-α e seu polimorfismo genético em pacientes HIV positivos, portadores de lipodistrofia e em uso de terapia anti-retroviral - PINHEIRO, Miguel Corrêa (Universidade Federal do Pará, 2013)
This work presents the results of the research entitled Levels of TNF-α and its Genetic Polimorfism in Patient Positive HIV, Bearers of Lipodistrophy and in Use of Anti-retroviral Therapy. It was aimed at, through the research for now presented, to study the levels serics of TNF-α and its Genetic Polymorphism in Patient Positive HIV, Bearers of lipodistrophy and in Use of Anti-retroviral Therapy. The need of know better the factors involved in the development of a syndrome clinic known as lipodistrophy justifies that aims, considered an adverse effect of the anti-retroviral therapy, so that that knowledge oportunize the reliable of a safe therapeutic regime, propitiating, in that way, a possible improvement in the quality of the patients' life. The methodology undertaken for the quantitative determination of the serics levels of TNF-α it was used of the ELISA method, while, tends in view the research of the occurrence of the polymorphism, it was used of the reaction of PCR for the extraction of DNA, followed by the digestion for the restriction enzyme Ncol. Forty patients participated of the present researches, which 26 were male and 14 were female. In this patient, the dosing of the TNF-α levels was proceeded, as well as it researches of the presence or absence of the genetic polymorphism (-308A).